Optimalisasi Penugasan Tidak Normal Menggunakan Metode Hungarian Maksimasi dan Minimisasi pada PT Abadi - Pesta Gultom; Elisma Putri Br Barus; Jupita Mariana Manullang; Emriahta Br Damanik; Ribka Nduru (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study explores the optimization of non-normal assignments utilizing the Hungarian method for both maximization and minimization. The Hungarian algorithm is a combinatorial optimization technique that efficiently solves assignment problems, ensuring optimal allocation of resources. By applying this method to non-normal assignment scenarios, we aim to demonstrate its effectiveness in enhancing productivity and reducing costs in various industries. The findings indicate that the Hungarian method can significantly improve decision-making processes in complex assignment frameworks, leading to more efficient operations.